2021
DOI: 10.1155/2021/6685468
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Involvement of Mitochondrial Dynamics and Mitophagy in Sevoflurane‐Induced Cell Toxicity

Abstract: General anesthesia is a powerful and indispensable tool to ensure the accomplishment of surgical procedures or clinical examinations. Sevoflurane as an inhalational anesthetic without unpleasant odor is commonly used in clinical practice, especially for pediatric surgery. However, the toxicity caused by sevoflurane has gained growing attention. Mitochondria play a key role in maintaining cellular metabolism and survival. To maintain the stability of mitochondrial homeostasis, they are constantly going through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 89 publications
(111 reference statements)
0
14
0
Order By: Relevance
“…Even the function of Sev on ferroptosis and mitophagy in cancers has not been reported, although some research demonstrated that Sev induced ferroptosis and mitophagy in other disease models. Exposure of Sev in young age mice was found to trigger mitophagy ( 40 ). Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Even the function of Sev on ferroptosis and mitophagy in cancers has not been reported, although some research demonstrated that Sev induced ferroptosis and mitophagy in other disease models. Exposure of Sev in young age mice was found to trigger mitophagy ( 40 ). Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been previously described for sevoflurane in experimental studies [ 14 , 45 , 46 ]. To clarify whether the CMRO 2 decrease by 4% sevoflurane might be related to mitochondrial impairment, we performed FAD imaging to monitor mitochondrial redox state while measuring [K + ] o as a correlate for neuronal activity and [Ca 2+ ] o as the main trigger for intracellular metabolic activation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the important members of the autophagy family, macroautophagy (MA), mitophagy (mA) [47][48][49] and CMA [49][50][51][52], CMA starts with HSC70, and HSC70 targets cargo proteins and then binds to LAMP2A to translocate the proteins into the lysosomal lumen. CMA activity is detectable under basal conditions in most cells, but overactivation occurs during stress, such as nutrient deprivation [53] and lipid overload [54,55].…”
Section: Discussionmentioning
confidence: 99%